Geometric analysis of the maloca of indigenous people of the Xingu - F., Spindola; M., Miranda (Seven Editora, 2023)
In this work, we make a parallel between the mathematical theory of the lines of curvature on the famous Ellipsoid of Monge, and the traditional knowledge of the indigenous peoples of the Xingu. These peoples, in the construction of their collective residence, called maloca, make use of support structures whose designs coincide with what the mathematical theory tells us of curvature lines and umbilical points on an ellipsoid with three distinct axes. We also emphasize the symbology of the maloca for the peoples of the Xingu, which represents a living animal or man (anthropomorphic). DOI: https://doi.org/10.56238/devopinterscie-020